Evaluasi Manajemen Pemeliharaan Berbasis RCM untuk Peralatan Produksi Berkategori Vital terhadap Keselamatan (Criticality A) dan Proses Produksi (Criticality B) pada PT. EMC di Kabupaten Bojonegoro - Purwanto, Andi; Megasari, Aisyah Darti; Nuryadi, Nuryadi (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The objective of this research is to evaluate RCM based production equipment categorized as Criticality A and B at PT EMC, Bojonegoro District. Research type is Qualitative Descriptive. Data collection technics are Interviews, Observations, and Documentations. Data analysis technics are Data Collection, Data Presentation, and Inference. Credibility method is used for data validation by extending the observation time and increasing accuracy. Research concluded that maintenance management at PT EMC is excellently applied. Maintenance program design are align with RCM manual, and even complemented by including several additional variables. The maintenance management program is well implemented and executed albeit there are room for improvements for future implementation.